Panjang Karapas dan Laju Pertumbuhan Spesifik Kepiting Bakau (Scylla serrata) yang diberi Jenis Pakan Berbeda di Area Ekowisata Kampung Kepiting, Bali - Suryani, Ni Desak Putu Ida; Julyantoro, Pande Gde Sasmita; Dewi, Ayu Putu Wiweka Krisna (Journal of Marine and Aquatic Sciences; Vol 4 No 1 (2018), 2017)
Mangrove forest is tropical coastal vegetation that grow on muddy and sandy soils which affected by sea tides. One of important commercial species that live in mangrove ecosystem is the mud crab ( Scylla serrata ). Feed and water quality have been considered as critical components for supporting the growth both of weight and carapace length of this species. This study was conducted from January to February 2017 in the area of ??Ecotourism Kampung Kepiting, Bali. The influence of different natural feed such as Jerbung shrimp ( Penaeus merguiensis ), Mollusca, lemuru fish ( Sardinella lemuru ) and sea worms ( Nereis sp . ) on the growth performance of the mud crab were investigated. Water quality parameter data such as pH, DO, temperature, salinity and ammonium were also collected. The obtained data were analyzed by using variance analysis of Statistical Product and Service Solutions (SPSS) version 21. The result showed that the use of different types of feed have no effect on  the length of carapace, but it has significantly influence on  the specific growth rate of mud crab. Finally, different types of the given feeding were still resulted in the save range of water quality parameters for mud crab culture.